Analisis Profitabilitas Usaha Penggilingan Padi di UD Dadi Mulyo Kabupaten Jepara - Nasution, Luqmanul Hakim. S.; Setiadi, Agus; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rice milling plays a crucial role in maintaining rice quality and business profitability. UD Dadi Mulyo, which has focused on glutinous rice production since 2021, faces various economic and market challenges affecting its sustainability. This study aims to analyze production costs, revenue, income, and the profitability of the rice milling business at UD Dadi Mulyo, Jepara Regency. The findings are expected to provide valuable insights for the company to evaluate its business performance and make strategic decisions. The research was conducted from November to December 2024 using a case study approach. The research location was purposively selected because UD Dadi Mulyo shifted its focus from regular rice to glutinous rice in 2021 due to declining demand for regular rice. Data analysis includes calculating production costs, revenue, income, and profitability ratios, including Gross Profit Margin (GPM), Net Profit Margin (NPM), and Return on Investment (ROI). The results were compared with bank deposit interest rates and industry standards using a one-sample t-test. The study found that the business has a higher ROI than bank deposit interest rates, but its GPM and NPM remain below industry standards. The one-sample t-test confirmed that the business's profitability is lower than the industry average in terms of GPM and NPM. These findings provide insights for the company to improve cost efficiency and marketing strategies to enhance business profitability.